Development of a Local Wisdom-based Religious Counseling Model in Reducing Student Bullying Behavior - Abdul Munir; Miswanto; Nur Arjani (Britain International for Academic Research (BIAR) Publisher, 2023)
The purpose of this research is to develop a model of religious counseling based on local wisdom in reducing bullying behavior. This research is research development (Research & Development). The development model used is the ADDIE Model (analyze, design, development, implementation, evaluation). The results of the development were validated by 2 counseling experts in order to obtain validation and reliability of the local wisdom-based religious counseling model. Next, a limited trial was carried out through experiments on 10 (ten) bullying students. The instruments used were expert validation sheets, questionnaires about bullying behavior, and student response questionnaires about the local wisdom-based religious counseling they received. Data were analyzed using qualitative and quantitative descriptive analysis techniques. The results of the validation test by 2 (two) counseling experts were categorized as good (75%). Notes and suggestions for improvement include highlighting religious values and local wisdom and telling more folklore related to friendship. Furthermore, based on input and comments from the 2 counseling experts, a revision of the religious counseling model based on local wisdom was carried out in phase I. The implementation phase will end with an evaluation, namely revision in phase II. Based on the data from the trial results through experiments on bullying students, the result was a reduction in bullying behavior with a difference in pretest and posttest scores of 52%. Then tested through the Wilcoxon test, obtained a significant value of 0.005 less than 0.05, it means that there is a significant difference between the pretest and posttest values. Students' responses to the local wisdom-based religious counseling that they attended were generally categorized as fun, interesting, clear and easy to understand. Overall, it can be concluded that the developed local wisdom-based religious counseling model is able to reduce student bullying behavior.